Sildenafil is Safe and Effective for the Treatment of Lower Ureteric Stone with no Major Side Effect - KC, Sudeep Raj; Timilsina, Bhusan Raj; Upadhyay, Hari Prasad; Devkota, Gaurav; Shah, Rajiv; Lamichanne, Nirmal (Birat Journal of Health Sciences, 2019)
INTRODUCTION: Urolithiasis is one of the most common diseases of the urinary tract. Prevalence of urinary stones in a life time is approximately 1% to 15%.Peak age of incidence is 30 years. Male are more commonly affected than female about 2 to 3 times. At the time of presentation 20 % of the calculi are found in the ureter, among which 70% are located in the distal third of the ureter.OBJECTIVE: To study the effect of sildenafil citrate on passage of stone from distal ureter.METHODOLOGY: This is the Quasi experimental study performed in College Of Medical Sciences, Chitwan, Nepal, from February 2017 to February 2018 for a period of one year. First 100 patients of urolithiasis were selected and divided into two groups with the help of lotiery method Group A and Group B. In group A we had patient on placebo and in group B we had patient receiving sildenafil 50 mg once daily and for the period of two weeks.RESULTS: The mean ± standard deviation of stone size was 7.01±1.70mm for treatment group and 6.85±1.56mm for placebo group (p> 0.64) .The stone expulsion rate was 74.5% for treatment group and 41.7% for placebo group (P